Determination of the optimum extraction pressure in a steam power cycle with only one bleed - L. Sanz-Prada; M. B. Folgueras-Díaz; M. Alonso-Hidalgo; S. Lage-Cal (Energy Reports, 2020)
In the years to come, a spectacular increase in electricity usage is foreseeable, partly due to the expansion of digital technologies and electric vehicles. Additionally, humankind must face the challenge of sustainable development. In this type of scenario, a significant proportion of electricity may be still generated by steam power cycles, but the usage of renewable energies, waste fuels and heat as energy sources will probably become more common. For some heat sources and depending on their characteristics, less regenerative cycles, i.e. with a lower number of steam extractions than those of the coal-fired power plants, are needed. In general, steam cycles have low thermal efficiency and a high number of hours of operation, which is why establishing an adequate criterion and method for choosing their parameters in the design conditions is of the utmost importance. Thus, with the design of plants in mind, the aim of this research is to propose an equation for choosing the pressure of the steam extraction of a regenerative steam power cycle with only one bleed that is driven to a deaerator. Based on a combination of thermal efficiency and economics, an equation that optimizes the pressure of the steam extraction has been obtained.
Keywords: 330; Deaerator; Extraction pressure; Net power; Steam power cycle; Thermal efficiency